CFD modeling on the chemical absorption of CO2 in a microporous tube-in-tube microchannel reactor. (1st November 2022) - Li, Wen-Ling; Liang, Hong-Wei; Wang, Jian-Hong; Shao, Lei; Chu, Guang-Wen; Xiang, Yang
Highlights: A CFD model combining the mesoscale mass transfer model with chemical reaction kinetics was used for chemical absorption for the first time. The errors between the simulation results and the experimental data were within ± 20%. The predicted local x CO2 (l) was used to calculate the K G a for the second-order irreversible reaction. The K G a of MTMCR was much higher than that of RPB under similar operating conditions. Abstract: In this paper, combining recently developed mesoscale mass transfer model with reaction kinetics, the chemical absorption process of CO2 by MEA solution in a microporous tube-in-tube microchannel reactor (MTMCR) was numerically simulated for the first time. The predicted values by CFD simulations were in agreement with the public experimental data (Na-Na Gao et al., Ind. Eng. Chem. Res., 2011). The distributions of CO2 removal efficiency and volumetric mass transfer coefficient under different gas flow rate, solvent flow rate, solvent temperature, and MEA concentration were analyzed. Among these factors, MEA concentration had a more significant influence on the CO2 chemical absorption. The K G a in the MTMCR was more than 200 times of that in the randomly packed bed under the similar operating conditions. The local mass transfer rate of chemical absorption was one order of magnitude higher than that of physical absorption. This research work could lay a theoretical foundation for the simulation of the complex gas–liquid systems including the chemical absorption by CFD method.